ANALISIS PRODUKSI DAN AGROINDUSTRI PISANG AMBON DALAM KAITANNYA DENGAN PENINGKATAN PENDAPATAN USAHATANI DI KABUPATEN GOWA - Palisuri, Palipada (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
Analysis of Production and Agroindustry of Ambonese Bananas with respectto the Increasing of Farming Income in Gowa Regency. This research aimed toascertain the influence of each production factor on production level of freshAmbonese bananas, and to know the feasibility of management handling ofAmbonese bananas product through household agroindustry activities.The result of the analysis revealed that the composition of using productioninput on the Ambonese bananas farming in Gowa regency was in the increasingreturn to scale. Based on the result of statistical test, it could be indicate thatthe use of seeds was relatively efficient, whereas the zuse of other productionfactors were relatively unefficient. The result of the Ambonese bananas sale wasrelatively profitable as stated by R/C ratio value for 4,08.